An exergy-based energy efficiency analysis on gas production from gas hydrates reservoir by brine stimulation combined depressurization method. (15th September 2021) - Wang, Xiao-Hui; Chen, Yun; Li, Xing-Xun; Xu, Qiang; Kan, Jing-Yu; Sun, Chang-Yu; Chen, Guang-Jin
Abstract: Before performing commercial scale production of natural gas hydrates (NGHs), it is inevitable to estimate the productivity, production period, optimal operation parameters, and further evaluate the technical and economic feasibilities of NGHs field production. The dissociation of gas hydrates is an endothermic process. This needs to compensate additional energy, such as chemical energy, geothermal energy and electricity, etc., in order to keep high dissociation rate. Exergy is a basic parameter that used for various energy systems as a potential tool for design, analysis and optimization. This work provided an exergy analysis method to evaluate the economic efficiency of NGHs exploitation process by brine stimulation combined depressurization method. The input data including cumulative volume of gas production, mass of water production and gas-to-water ratio was obtained by the numerical simulation of TOUGH + HYDRATE. Through the exergy analysis, the total productivity and production period could be determined. These have rarely been reported. The influences of operation parameters, such as well spacing, injection temperature and injection rate of brine on net exergy production were investigated for guiding the set of optimal operating conditions. Since the cost may be one of the biggest challenges for NGHs production, this work suggests making full use of all kinds low-level energy sources to improve energy efficiency, such as brine with high concentration produced by desalination, tidal energy, wind energy, etc. Highlights: An exergy analysis method was established to evaluate the energy efficiency of hydrate production. The productivity, production period and EER could be determined through exergy analysis. Exergy analysis can be a tool to guide the set of optimal operating conditions. Integrating with low-level energy sources to improve economic efficiency.